2017
DOI: 10.1007/978-1-4939-6813-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Modeling Brassinosteroid-Mediated Signaling in Plant Development

Abstract: Mathematical modeling of biological processes is a useful tool to draw conclusions that are contained in the data, but not directly reachable, as well as to make predictions and select the most efficient follow-up experiments. Here we outline a method to model systems of a few proteins that interact transcriptionally and/or posttranscriptionally, by representing the system as Ordinary Differential Equations and to study the model dynamics and stationary states. We exemplify this method by focusing on the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This suggests that interactions between BZR and DELLA exert more influence over the dynamics of the pathways than BZR-mediated biosynthesis of GA and are more likely to be able to promote any effective change in the behaviour of the signalling processes. Numerical results also demonstrated that for all parameter sets where solutions tended to a steady state, the solutions of model (10), (12)- (14) and the averaged over space solutions of model (7), (8), (15)- (19) exhibit similar dynamics, although spatially heterogenous steady-states are obtained for BR and GA concentrations, Fig. 18.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This suggests that interactions between BZR and DELLA exert more influence over the dynamics of the pathways than BZR-mediated biosynthesis of GA and are more likely to be able to promote any effective change in the behaviour of the signalling processes. Numerical results also demonstrated that for all parameter sets where solutions tended to a steady state, the solutions of model (10), (12)- (14) and the averaged over space solutions of model (7), (8), (15)- (19) exhibit similar dynamics, although spatially heterogenous steady-states are obtained for BR and GA concentrations, Fig. 18.…”
Section: Discussionmentioning
confidence: 81%
“…The BR and GA signalling pathways have a diverse range of effects on plant growth and developmental processes, some of which overlap. To examine the behaviours of these signalling pathways and their interactions we developed mathematical models of the BR signalling pathway, and crosstalk between the BR and GA pathways under assumptions of both spatial homogeneity: models (1) and (10), (12)- (14), and spatial heterogeneity of signalling processes: models (7)-(9) and (7), (8), (15)- (19). Tables 1 and 3 and β z = 10 µM −1 min −1 , γ z = 0.133 min −1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations